(untitled) (Journal of the College of Basic Education, 2022)
The reputation of George Eliot ( 18191880) rests mainly on her novels Adam Bede 1859, The Mill on the Floss 1860, Silas Marner 1861 and Middlemarch 1871. In Adam Bede George Eliot examines the driving forces of her characters who suffer from their inherent egoism and selfdeception. The Mill on the Floss is a detailed study of a girl’s growth towards maturation